Preparation method and application of semimetal carbon nitride

By preparing semi-metallic carbon nitride, the problem of insufficient CO2 adsorption capacity and photogenerated electron-hole pair separation ability of existing graphite carbon nitride photocatalytic materials has been solved, and efficient photocatalytic reduction of CO2 to prepare hydrocarbon chemicals has been achieved. Effect.

CN119327500APending Publication Date: 2025-01-21JIANGSU UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411444436.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing graphite carbon nitride photocatalytic materials have weak adsorption ability to CO2, and their light absorption ability and photogenerated electron-hole pair separation ability are poor.

Method used

Using specific Murbisyl methane sodium methane and chloride 1-clone-3-methimimazole dissolved in ionic water, mixes in a magnetic mixer, then evaporates solvents in vacuum drying boxes, uses acetone, uses acetone, uses acetone, uses acetone, uses acetone, uses acetone, uses acetone, uses acetone, and uses acetone. Purification, finally burn and grind the ball in the atmosphere of the pupa, prepare semi -metal carbon nitride.

Benefits of technology

The prepared semimetallic carbon nitride has excellent CO2 adsorption capacity and photocatalytic activity, can effectively separate photogenerated electron-hole pairs, and improve the efficiency of photocatalytic reduction of CO2 to produce hydrocarbon chemicals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327500A_ABST
    Figure CN119327500A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of photocatalysis, in particular to a preparation method and application of semimetal carbon nitride, and the preparation method comprises the following steps: dissolving sodium tricyanomethanate and 1-butyl-3-methylimidazole chloride in deionized water, stirring and mixing; evaporating the mixed solution in a vacuum drying box to remove a solvent so as to obtain mixed residues, dissolving with acetone, centrifuging, evaporating supernate in the vacuum drying box, and purifying with acetone so as to obtain light yellow oily liquid; spreading the faint yellow oily liquid in a ceramic ark, calcining in an argon atmosphere, and cooling to room temperature to obtain a black solid; the black solid is ground into powder, then the powder is treated in a ball milling tank, black fine powder is obtained, the black fine powder is alternately washed with deionized water and absolute ethyl alcohol and dried, and the semi-metal carbon nitride is obtained.The semi-metal carbon nitride prepared through the method has the excellent charge transfer capacity, separation of photo-induced electron-hole pairs is facilitated, and the semi-metal carbon nitride has a good application prospect. And due to the electron-rich characteristic and abundant nitrogen atoms, the material has excellent CO2 adsorption capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photocatalysis technology, and in particular to a preparation method and application of semi-metallic carbon nitride. Background Art

[0002] The content of various dyes, drugs (intermediates) and other difficult-to-degrade organic pollutants in industrial wastewater is increasing, posing a serious threat to the environment and human health. At present, methods such as adsorption, membrane separation, and chemical oxidation are all used in the treatment of such wastewater. Among them, chemical oxidation reactions have attracted widespread attention because of their strong oxidizing ability to quickly remove difficult-to-degrade organic matter. Photocatalysis is a type of advanced oxidation, and its reaction source driving force is sunlight. The degradation process is green, clean, and has little pollution. It has great application potential in the removal of difficult-to-degrade organic matter.

[0003] In the past few decades, the excessive CO2 produced by the massive combustion of fossil fuels has brought about serious environmental and energy crises. Photocatalysis driven by solar energy can directly convert CO2 and H2O into high-value-added chemicals and fuels under mild conditions. Graphitic carbon nitride (g-C3N4), as a semiconductor material with stable properties and suitable band gap, has a wide range of applications in the field of photocatalysis.

[0004] However, the actual adsorption capacity of g-C3N4 for CO2 is weak, and its light absorption capacity and the ability to separate photogenerated electron-hole pairs need to be further improved. Therefore, it is necessary to develop a new type of carbon nitride material for photocatalytic CO2 reduction. Summary of the invention

[0005] The purpose of the present invention is to provide a preparation method and application of semi-metallic carbon nitride, aiming to solve the problems of weak CO2 adsorption capacity, poor absorption capacity and separation capacity of photogenerated electron-hole pairs of existing graphite carbon nitride photocatalytic materials.

[0006] To achieve the above objectives, in a first aspect, the present invention provides a method for preparing semi-metallic carbon nitride, comprising the following steps:

[0007] Dissolving sodium tricyanomethanide and 1-butyl-3-methylimidazole chloride in a specific molar ratio in deionized water, and stirring and mixing in a magnetic stirrer under a certain temperature condition to obtain a mixed solution;

[0008] The mixed solution is placed in a vacuum drying oven to evaporate the solvent, a mixed residue is obtained, and acetone is used to dissolve it, solids are removed by centrifugation, the supernatant is placed in a vacuum drying oven to evaporate, and acetone is used to purify it again until no solids remain, thereby obtaining a light yellow oily liquid;

[0009] The light yellow oily liquid is spread evenly in a ceramic ark, the ceramic ark is wrapped with tin foil, and then placed in the center of a quartz glass tube, and heated to a specified temperature and calcined for a certain time under an argon atmosphere, and after cooling to room temperature, a black solid with a bright metallic luster is obtained;

[0010] The black solid is ground into powder, and then transferred to a ball mill for further processing to obtain black fine powder, which is then washed alternately with deionized water and anhydrous ethanol and dried to obtain semi-metallic carbon nitride.

[0011] The molar ratio of the sodium tricyanomethanide to the 1-butyl-3-methylimidazole chloride is 1:0.9-1.1; the final concentrations of the sodium tricyanomethanide and the 1-butyl-3-methylimidazole chloride in the mixed solution are 0.32-0.35 mol / L, the stirring time of the mixing in the magnetic stirrer is 10-12 h, the stirring rate is 500-600 r / min, and the temperature during stirring is 20-30° C.

[0012] The temperature of the vacuum drying oven is 60-70°C, the evaporation time is 24-30h, the argon flow rate used during calcination is 250-350sccm, the heating rate is 10°C / min, the calcination temperature is 400°C, and the calcination time is 1h.

[0013] The grinding time is 15 to 30 minutes, the ball milling time is 30 minutes, and the prepared semi-metallic carbon nitride is micron-sized particles with uniform morphology and size, and a diameter of 1 to 3 μm.

[0014] In a second aspect, the present invention further provides an application of semi-metallic carbon nitride, which is prepared by the method for preparing semi-metallic carbon nitride as described in the first aspect above, and is characterized in that the semi-metallic carbon nitride is used in photocatalytic reduction of carbon dioxide to produce hydrocarbon chemicals.

[0015] The invention discloses a method for preparing semi-metallic carbon nitride, comprising dissolving sodium tricyanomethanide and 1-butyl-3-methylimidazole chloride in a specific molar ratio in deionized water, and stirring and mixing in a magnetic stirrer under a certain temperature condition to obtain a mixed solution; placing the mixed solution in a vacuum drying oven to evaporate the solvent, obtaining a mixed residue, dissolving it in acetone, centrifuging to remove solids, placing the supernatant in a vacuum drying oven to evaporate, and purifying it again with acetone until no solids remain, to obtain a light yellow oily liquid; spreading the light yellow oily liquid in a ceramic ark, wrapping the ceramic ark with tin foil, and then placing it in the center of a quartz glass tube, heating it to a specified temperature in an argon atmosphere, and calcining it for a certain time. The method comprises the following steps: grinding the black solid into powder, transferring the powder to a ball mill for further treatment, obtaining a black fine powder, washing the powder with deionized water and anhydrous ethanol alternately, and drying the powder to obtain a semi-metallic carbon nitride. The method is simple and controllable, has a high yield, and the raw materials are cheap and readily available. The method uses a polycationic ionic liquid as a template and a reaction source, mixed with tricyanomethane anions, and calcined and ball milled to prepare a semi-metallic carbon nitride (hm-C4N3). The prepared hm-C4N3 is a micron-sized particle with a diameter of 1 to 3 μm, and its skeleton is composed of coplanar conjugated triazine rings, and the center is connected by carbon atoms. The spin polarization of the central carbon atom (the spin-down band crosses the Fermi level, showing metallic properties, while the spin-up band is below the Fermi level, showing semiconductor properties) enables this metal-free semi-metallic material to have excellent charge transfer capabilities, which helps to separate photogenerated electron-hole pairs, thereby improving photocatalytic activity. In addition, its electron-rich properties and abundant nitrogen atoms give it excellent CO2 adsorption capacity, and it has broad application prospects in the field of photocatalytic carbon dioxide reduction and conversion to prepare hydrocarbon chemicals, solving the problems of existing graphite carbon nitride photocatalytic materials having weak CO2 adsorption capacity, poor absorption capacity and poor separation capacity of photogenerated electron-hole pairs. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0017] Figure 1 SEM image of hm-C4N3 prepared in the present invention

[0018] Figure 2 This is the XRD pattern of hm-C4N3 prepared in the present invention.

[0019] Figure 3 The activity of hm-C4N3 prepared in the present invention in reducing CO2 under ultraviolet visible light irradiation.

[0020] Figure 4 The present invention provides a flow chart of a method for preparing semi-metallic carbon nitride. DETAILED DESCRIPTION

[0021] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0022] See also Figures 1 to 4 In a first aspect, the present invention provides a method for preparing semi-metallic carbon nitride, comprising the following steps:

[0023] S1: dissolving sodium tricyanomethanide and 1-butyl-3-methylimidazole chloride in a specific molar ratio in deionized water, and stirring and mixing in a magnetic stirrer under a certain temperature condition to obtain a mixed solution;

[0024] In an embodiment of the present invention, the 1-butyl-3-methylimidazole chloride can be replaced with 1-butyl-3-methylimidazole bromide, and the molar ratio of the sodium tricyanomethanide to the 1-butyl-3-methylimidazole chloride is 1:0.9-1.1; the final concentration of the sodium tricyanomethanide and the 1-butyl-3-methylimidazole chloride in the mixed solution is 0.32-0.35 mol / L, the stirring time of the mixing in the magnetic stirrer is 10-12 h, the stirring rate is 500-600 r / min, and the temperature during stirring is 20-30°C.

[0025] S2: placing the mixed solution in a vacuum drying oven to evaporate the solvent, obtaining a mixed residue, dissolving it with acetone, removing solids by centrifugation, evaporating the supernatant in a vacuum drying oven, and purifying it again with acetone until no solids remain, to obtain a light yellow oily liquid;

[0026] In the embodiment of the present invention, the temperature of the vacuum drying oven is 60-70° C., the evaporation time is 24-30 h, the rotation speed during centrifugation is 8000-10000 r / min, the centrifugation time is 3-5 min, the amount of acetone used during purification is 5-10 ml, and the number of purification times is 3-5 times.

[0027] S3: Spread the light yellow oily liquid in a ceramic ark, wrap the ceramic ark with tin foil, and then put it in the center of a quartz glass tube. In an argon atmosphere, heat it to a specified temperature and calcine it for a certain time. After cooling to room temperature, a black solid with a bright metallic luster is obtained.

[0028] In the embodiment of the present invention, the argon gas flow rate used during the calcination is 250-350 sccm, the heating rate is 10° C. / min, the calcination temperature is 400° C., and the calcination time is 1 hour.

[0029] S4 grinds the black solid into powder, transfers it to a ball mill for further processing, obtains black fine powder, and washes it alternately with deionized water and anhydrous ethanol, and dries it to obtain semi-metallic carbon nitride.

[0030] In the embodiment of the present invention, the grinding time is 15 to 30 minutes, the ball milling time is 30 minutes, and the prepared semi-metallic carbon nitride is micron-sized particles with uniform morphology and size, and a diameter of 1 to 3 μm.

[0031] In a second aspect, the present invention further provides an application of semi-metallic carbon nitride, which is prepared by the method for preparing semi-metallic carbon nitride as described in the first aspect above, and is characterized in that the semi-metallic carbon nitride is used in photocatalytic reduction of carbon dioxide to produce hydrocarbon chemicals.

[0032] In order to better understand the present technical solution, the following embodiments are provided for further explanation:

[0033] Unless otherwise specified, the experimental methods used in the examples are all conventional methods, and the materials, reagents, etc. used in the examples are all commercially available unless otherwise specified.

[0034] Embodiment 1:

[0035] Accurately weigh 1.13g (0.01mol) of sodium tricyanomethanide and 1.75g ​​(0.01mol) of 1-butyl-3-methylimidazole chloride in a 50ml beaker, add 30ml of deionized water, place on a magnetic stirrer, set the stirring rate to 550r / min, the temperature to 25℃, stir for 12h, and place in a 60℃ vacuum drying oven for 30h to remove the solvent. The obtained residue was transferred to a centrifuge tube, 10ml of acetone was added, and the precipitate was removed by centrifugation at a speed of 8000r / min. The supernatant was placed in a 60℃ vacuum drying oven again to evaporate the solvent. Purify with acetone 4 times according to the same procedure, and finally dry for 24h to obtain a clear and transparent light yellow oily precursor. Spread the oily precursor flat in a ceramic ark and wrap it with tin foil to prevent the sample from falling. Then put it in the center of the quartz glass tube, and in an argon atmosphere, heat it from room temperature to 400°C at a rate of 10°C / min and keep it for 1 hour. After cooling to room temperature, a large black solid with bright metallic luster is obtained. The large solid is ground in an agate mortar for 20 minutes, and then transferred to a ball mill to continue the reaction for 30 minutes to obtain a black fine powder solid. Finally, it is washed alternately with deionized water and anhydrous ethanol for 3 times, and hm-C4N3 is obtained after drying.

[0036] Figure 1 This is a SEM image of hm-C4N3 synthesized in Example 1. As can be seen from the figure, the prepared hm-C4N3 is in granular form, with a particle size of 1-3 μm and a uniform size distribution.

[0037] like Figure 2 As shown, the structure test of the prepared samples was carried out on a German Bruker D8 X-ray diffractometer (Cu-Kα radiation, The range is 10°-80°), and the scanning rate is 7°min -1 As can be seen from the figure, the hm-C4N3 synthesized in Example 1 has a broad peak near 26°, corresponding to its (0 0 2) plane, reflecting the interlayer stacking structure and weak crystallinity of its conjugated aromatic system.

[0038] Embodiment 2:

[0039] Accurately weigh 0.565g (0.005mol) sodium tricyanomethanide and 1.096g (0.005mol) 1-butyl-3-methylimidazole bromide in a 50ml beaker, add 15ml deionized water, place on a magnetic stirrer, set the stirring rate to 550r / min, the temperature to 25℃, stir for 10h, and place in a 60℃ vacuum drying oven for 24h to remove the solvent. The obtained residue was transferred to a centrifuge tube, 5ml acetone was added to dissolve, and the solid was removed by centrifugation at 10000r / min. The supernatant was placed in a 60℃ vacuum drying oven again to evaporate the solvent. Purify with acetone three times according to the same procedure, and finally dry for 24h to obtain a light yellow oily precursor. Spread the oily precursor flat in a ceramic ark and wrap it with tin foil to prevent the sample from falling. Then put it in the center of the quartz glass tube, and in an argon atmosphere, heat it from room temperature to 400°C at a rate of 10°C / min and keep it for 1 hour. After cooling to room temperature, a large black solid with bright metallic luster is obtained. The large solid is ground in a mortar for 15 minutes, and then transferred to a ball mill to continue the reaction for 30 minutes to obtain a black fine powder solid. Finally, it is washed alternately with deionized water and anhydrous ethanol for 3 times, and hm-C4N3 is obtained after drying.

[0040] Embodiment 3:

[0041] The hm-C4N3 prepared in Example 1 was used to reduce CO2 to prepare hydrocarbon chemicals under visible light irradiation: under irradiation of a 300W xenon lamp, the activity was tested for 5 hours in a mixed solution of triethanolamine and water (4ml triethanolamine and 12ml water) with a volume ratio of 1:3. The amount of hm-C4N3 catalyst was 10mg, the temperature of the reaction system was 10°C, the CO2 pressure was 0.85MPa, and the stirring rate was 350r / min. The yields of CH4 and CO were finally obtained by gas chromatography. Figure 3 shown.

[0042] The above disclosure is only a preferred embodiment of the preparation method and application of a semi-metallic carbon nitride of the present invention, and it is certainly not intended to limit the scope of the present invention. A person skilled in the art can understand that all or part of the processes of the above embodiments and equivalent changes made according to the claims of the present invention still fall within the scope of the invention.

Claims

1. A method for preparing semi-metallic carbon nitride, characterized in that: The following steps are involved: Dissolving sodium tricyanomethanide and 1-butyl-3-methylimidazole chloride in a specific molar ratio in deionized water, and stirring and mixing in a magnetic stirrer under a certain temperature condition to obtain a mixed solution; The mixed solution is placed in a vacuum drying oven to evaporate the solvent, a mixed residue is obtained, and acetone is used to dissolve it, solids are removed by centrifugation, the supernatant is placed in a vacuum drying oven to evaporate, and acetone is used to purify it again until no solids remain, thereby obtaining a light yellow oily liquid; The light yellow oily liquid is spread evenly in a ceramic ark, the ceramic ark is wrapped with tin foil, and then placed in the center of a quartz glass tube, and heated to a specified temperature and calcined for a certain time under an argon atmosphere, and after cooling to room temperature, a black solid with a bright metallic luster is obtained; The black solid is ground into powder, and then transferred to a ball mill for further processing to obtain black fine powder, which is then washed alternately with deionized water and anhydrous ethanol and dried to obtain semi-metallic carbon nitride.

2. The method for preparing semi-metallic carbon nitride according to claim 1, characterized in that: The molar ratio of the sodium tricyanomethanide to the 1-butyl-3-methylimidazole chloride is 1:0.9-1.1; the final concentrations of the sodium tricyanomethanide and the 1-butyl-3-methylimidazole chloride in the mixed solution are 0.32-0.35 mol / L, the stirring time of the mixing in the magnetic stirrer is 10-12 h, the stirring rate is 500-600 r / min, and the temperature during stirring is 20-30° C.

3. The method for preparing semi-metallic carbon nitride according to claim 1, characterized in that: The temperature of the vacuum drying oven is 60-70°C, the evaporation time is 24-30h, the argon flow rate used during the calcination is 250-350sccm, the heating rate is 10°C / min, the calcination temperature is 400°C, and the calcination time is 1h.

4. The method for preparing semi-metallic carbon nitride according to claim 1, characterized in that: The grinding time is 15 to 30 minutes, the ball milling time is 30 minutes, and the prepared semi-metallic carbon nitride is micron-sized particles with uniform morphology and size, and a diameter between 1 and 3 μm.

5. An application of semi-metallic carbon nitride, wherein the semi-metallic carbon nitride is prepared by the method for preparing the semi-metallic carbon nitride according to any one of claims 1 to 4, characterized in that: The semi-metallic carbon nitride is used in photocatalytic reduction of carbon dioxide to produce hydrocarbon chemicals.

Citation Information

Cited By

  • Semi-metal carbon nitride / metal organic framework MIL-53Fe heterojunction photocatalyst as well as preparation method and application thereof

    CN122252265A